Simulation Studies on Heat Absorption of Container Green Roof Design Using BIM. - Wahab, Izudinshah; Nur Afifah Kasmion; Mohd Jamil Mohd Hamberi; Hazri Abd Aziz; Nor Azizah Adnan (Recent Trends in Civil Engineering and Built Environment, 2020)
In meeting the needs of the users for temporary buildings or houses, the use of containers in the construction industry has become one of a trendy contemporary solution. Due to its structure readiness and low cost advantage, containers are well used as commercial kiosks, office space and home shelter. However, containers are often associated with thermal problems related to indoor temperature increment especially in tropical region. Due to that, several thermal insulation techniques are introduced, mostly are indoor insulation panel cladding type. However, the physical condition of the container, especially the roof may determine the heat absorption level of the building. Based on a simulation study using Autodesk Revit Building Information Nodelling (BIM) software, this paper reports how types of roof design and green roof application may reflect on container’s heat absorption. A flat and curved roof were chose to be simulated based on standard 20ft x 40ft size of container where both were tested with and without the green roof application. The result shows that curved roof surface with green roof do produce a better heat absorption quality.